Hubungan Self Efficacy dengan Persiapan Kehamilan Sehat Pada Calon Pengantin Wanita - Nina, Nina Sefia Sari; Toyibah, Afnani; Apsari, Duhita Dyah; Triningsih, Reni Wahyu (Malang Journal of Midwifery (MAJORY), 2023)
Self-efficacy affects one's health behavior including behavior in preparing for pregnancy during the preconception period. Pregnancy that is not properly prepared can trigger various problems in pregnancy and childbirth such as; KEK, anemia, antepartum bleeding, and LBW. his study aims to determine the correlation between self efficacy and preparation for pregnancy of the premarital women. Correlational analytic design with a cross sectional approach was used in this study. Purposive sampling technique was used to obtain 57 respondents who met the inclusion criteria. This study used the Perceived Health Competence Scale (PHCS) and preparation for pregnancy questionnaire as the instrument for data collection. The results of the Spearman rank correlation test analysis showed a correlation coefficient of 0.359 with a significance level of 0.006 <0.05 which indicated that there was a moderate relationship between self-efficacy and preparation for a healthy pregnancy in prospective brides at KUA Lowokwaru, Malang. The higher the self-efficacy, the better the preparation for pregnancy. So, it is better to increase the provision of information regarding the importance of convincing oneself to manage health and prepare for pregnancy to adolescents.